Fostering Sport Sciences Students’ Academic Achievement through Peer Oriented Instruction - Birhan, Amare Tesfie; Chekol, Chalachew (Indonesian Journal of Curriculum and Educational Technology Studies, 2019)
The purpose of this study was to examine the perception of students, peer assisters and the department head towards peer assisted instruction. It also aimed to investigate the extent of its implementation in sport sciences department and challenges which hamper its effectiveness. The subjects were peer assisters, tutees and the department head. They were selected through purposive sampling technique. Questionnaire, interview and focus group discussions were employed as data gathering instruments. The findings indicated that tutees, peer assisters and the department head have positive perceptions toward peer assisted learning instruction. They perceived that peer assisted instructional approach helps learners to develop their academic achievement, to enhance their social interaction skills and to manage their psychological difficulties. However, the practices were limited to activities such as doing assignments and project works, sharing their learning and studying experience. The data also revealed that factors such as lack of tutees motivation, lack of facilities, lack of support from the department, lack of peer assister tutoring experience were the observed challenges which affect students’ engagement in peer assisted instructional model. Abstrak Kajian ini bertujuan untuk menelisik persepsi siswa, tutor sebaya dan pimpinan lembaga mengenai implementasi tutor sebaya dalam pembelajaran. Selain itu juga bertujuan untuk mengetahui implementasi dan tantangannya dalam bidang ilmu olah raga. Subjek penelitian ini meliputi para tutor sebaya, peserta program tutorial (tutee), dan kepala lembaga. Semua subjek diseleksi menggunakan teknik purposive sampling. Kuesioner, wawancara, dan diskusi terfokus juga dilakukan untuk mengumpulkan data. Penelitian ini menemukan bahwa tutee, tutor sebaya, dan kepala lembaga memiliki persepsi positif terhadap pembelajaran tutor sebaya. Mereka menyatakan bahwa pembelajaran tutor sebaya dapat meningkatkan kemampuan akademik, kecakapan sosial, dan dapat juga mengatasi hambatan psikologis siswa. Bagaimanapun juga, praktik pembelajaran ini masih sebatas pada aktivitas mengerjakan tugas dan pembelajaran berbasis proyek, termasuk juga berbagi pengalaman belajar mereka. Penelitian ini juga menemukan bahwa beberapa faktor seperti motivasi tutee, ketiadaan fasilitas, kurangnya dukungan dari lembaga, dan kurangnya pengalaman tutor teman sebaya turut memengaruhi keterlibatan siswa dalam pembelajaran. Keywords: academic achievement; challenges; perception; peer assisted instruction; sport science